EFEKTIFITAS INTERVENSI PEMBERDAYAAN KELUARGA DENGAN MODEL HOME CARE SERVICE TERHADAP MANAJEMEN DIRI PASIEN DIABETES MELITUS TIPE 2 - Surya, Defrima Oka (Universitas Udayana, 2023)
Type 2 DM can affect aspects of the sufferer's quality of life and has a risk of complications. DM requires continuous therapy to be able to control glucose levels properly, in addition to pharmacological therapy, non-pharmacological therapy is also needed to maximize blood glucose control, including in this case self-management measures. One of the efforts that can be made to improve the self-management of DM patients in managing their disease is through family empowerment with a home care service model. The purpose of this study was to examine the effect of family empowerment interventions using the home care service model on self-management of type 2 DM patients. The quasi-experimental research design used a one group pre and posttest approach without a control group. The research was conducted in the Andalas Padang Health Center Work Area. Sampling with consecutive sampling technique with a sample size of 19 people. The intervention was given for 2 weeks. Self-management was assessed using The Summary of Diabetes Self Care Activities (SDSCA) questionnaire. The results of the difference in self-management scores before and after giving the intervention amounted to 34.26. Based on the t-dependent test statistic (paired test) it was found that p value = 0.000 (?<0.05), meaning that the family empowerment intervention using the home care service model is effective in improving the self-management of type 2 DM patients. Family empowerment using the home care service model can be applied to community nurses to ensure continuity of patient care and prevent complications.